(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
In the current work included the production pressure distribution through moved elliptic fuel tank. The work included two aspects, in the first Finite Element Method with control volume has been created as by ANSYS software. In the second aspect, experiment model has been constructed to be tested in wind tunnel. The results of both theoretical and experimental aspects show that the distribution of the pressure showed that the increase being observed on the front cover and decayed through the longitudinal shell until reversed to be on the outward direction at the back cover. The comparison both the theoretical and experimental results indicated an accepted difference.